2001
DOI: 10.1053/jhep.2001.26815
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of oral entecavir given for 28 days in patients with chronic hepatitis B virus infection

Abstract: Entecavir is an oral antiviral drug with selective activity against hepatitis B virus (HBV). We conducted a randomized, placebo-controlled, dose-escalating study in patients with chronic hepatitis B infection in which we evaluated the efficacy and safety of entecavir given for 28 days. Follow-up was 24 weeks. All doses of entecavir (0.05 mg, 0.1 mg, 0.5 mg, and 1.0 mg) showed a pronounced suppression of replication of the HBV with a 2.21, 2.29, 2.81, and 2.55 mean log 10 reduction of viral load, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 21 publications
2
72
0
3
Order By: Relevance
“…60 Hence, the use of more potent nucleoside analogues is desirable. Several new nucleoside analogues, including adefovir dipivoxil, 61 entecavir, 62 and emtricitabine, 63 have been found to be effective in suppressing HBV replication. Additional clinical trials of these nucleoside analogues are needed to determine their antiviral efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
“…60 Hence, the use of more potent nucleoside analogues is desirable. Several new nucleoside analogues, including adefovir dipivoxil, 61 entecavir, 62 and emtricitabine, 63 have been found to be effective in suppressing HBV replication. Additional clinical trials of these nucleoside analogues are needed to determine their antiviral efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Entecavir (ETV; BMS-200475) is a novel deoxyguanosine analog with potent activity against HBV in vitro, in animal studies, and in patients chronically infected with HBV (7,11,14,17,21,23,29). In enzymatic studies, 3TC r HBV polymerases were shown to have reduced susceptibility to ETV (20).…”
Section: Entecavir (Etv) Exhibits Potent Antiviral Activity In Patienmentioning
confidence: 99%
“…Treatment with ADV, recently approved by the U.S. Food and Drug Administration, can be associated with dose-limiting nephrotoxicity (6), although the reported frequency of resistance to ADV is considerably lower than that to 3TC (2, 28). Therefore, more potent and safer oral therapies, with less frequent development of viral resistance, are needed for the treatment of chronic HBV infections.Entecavir (ETV; BMS-200475) is a novel deoxyguanosine analog with potent activity against HBV in vitro, in animal studies, and in patients chronically infected with HBV (7,11,14,17,21,23,29). In enzymatic studies, 3TC r HBV polymerases were shown to have reduced susceptibility to ETV (20).…”
mentioning
confidence: 99%
“…However, viral breakthrough is detected in approximately 16% to 32% of patients after 1 year of treatment (12). Newer oral nucleoside/nucleotide analogues in clinical trials, such as adefovir dipivoxil (4), entecavir (6), and emtricitabine (19,18), appear to be at least as potent as lamivudine. In vitro and in vivo studies showed that adefovir and entecavir are also effective in suppressing lamivudine-resistant HBV (8).…”
mentioning
confidence: 99%